North Sami snow concepts and snow terminology - Gaup Eira, Inger Marie; Magga, Ole Henrik; Eira, Nils Isak (Sámi dieđalaš áigečála, 2026)
This article is an introductory analysis of North Sami snow concepts and snow terminology, their use and definitions. The focus is on concepts used to communicate grazing conditions for reindeer on snow-covered ground. On the basis of terminological theory, and in particular on the basis of six basic elements of practical reindeer herding, the content and use of the most central snow concepts is discussed. The concepts seem to be linked to each other depending on which elements of reindeer herding they are used to describe and communicate. While scientific concepts and their definitions seek to be both clear and independent from their use in different contexts, the terminology of languages embedded in nature tend to carry much content derived from practical use. The article is a demonstration of the challenges everybody will face when attempting to define the conceptual content, because their content comprises both a central meaning, which is often intuitive, and connected to practical use, but also to communicative functions. In this respect, they differ in an important way from terms which have been developed to express scientifically defined concepts. A natural next step will be to compare these concepts with snow concepts developed for scientific use.